Acute Stent Migration into the Right Ventricle in a Patient with Iliac Vein Stenting - Holst, Torulv; Großwendt, Thorsten; Laham, Majd Makarious; Roosta-Azad, Mehdy; Zandi, Afsaneh; Kamler, Markus (The Thoracic and Cardiovascular Surgeon Reports, 2018)
Endovascular stent placement for chronic postthrombotic iliofemoral venous obstructive lesions is an effective therapeutic option and might be complicated by stent migration. We report a case of a venous stent that was lost from the iliac vein into the right ventricle rescued by emergent open-heart surgery.
Keywords: venous disease; endovascular procedures/stents; except PCI; heart failure; cardiopulmonary bypass; CPB